2013
DOI: 10.1088/0004-637x/764/1/3
|View full text |Cite
|
Sign up to set email alerts
|

Hα ACTIVITY OF OLD M DWARFS: STELLAR CYCLES AND MEAN ACTIVITY LEVELS FOR 93 LOW-MASS STARS IN THE SOLAR NEIGHBORHOOD

Abstract: Through the McDonald Observatory M Dwarf Planet Search, we have acquired nearly 3000 high-resolution spectra of 93 late-type (K5-M5) stars over more than a decade using the High Resolution Spectrograph on the Hobby-Eberly Telescope. This sample provides a unique opportunity to investigate the occurrence of long-term stellar activity cycles for low-mass stars. In this paper, we examine the stellar activity of our targets as reflected in the Hα feature. We have identified periodic signals for six stars, with per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
120
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 63 publications
10
120
2
Order By: Relevance
“…We find evidence for rotation periods of the order of 10-40 days and active regions lifetime cycles longer than ≃50 days. These findings are in agreement with previous results (Donahue et al 1997a,b;Reiners et al 2012;Robertson et al 2013) and are supported by a more detailed analysis we are currently preparing (Suárez Mascareño et al 2016, in prep …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We find evidence for rotation periods of the order of 10-40 days and active regions lifetime cycles longer than ≃50 days. These findings are in agreement with previous results (Donahue et al 1997a,b;Reiners et al 2012;Robertson et al 2013) and are supported by a more detailed analysis we are currently preparing (Suárez Mascareño et al 2016, in prep …”
Section: Discussionsupporting
confidence: 93%
“…9 for an example). Robertson et al (2013) found similar evidence analyzing the ∼11-year long series of Hα observations of a sample of 93 M-type dwarfs, and concluded that ∼10% of M dwarfs show either long-term trends or 1 year activity cycles.…”
Section: Ca II Handk Vs Hαmentioning
confidence: 59%
See 1 more Smart Citation
“…The spectroscopic activity diagnostics, namely the Full Width Half Maximum (FWHM) of the CCF, the ¢ R log HK index (Lovis et al 2011), and the Hα index (Gomes da Silva et al 2011;Robertson et al 2013), however, did not confirm this result, all suggesting instead a main periodicity around 14 days ( Figure 2). The auto correlation function on the K2 data, computed as described in McQuillan et al (2013) 36 also converged to 14 days.…”
Section: Stellar Activitymentioning
confidence: 95%
“…The Ca ii H&K lines are commonly used as optical activity proxies (e.g. Baliunas & Jastrow 1990;Baliunas et al 1998;Hall et al 2007), as are other lines, such as those of the Balmer series (Robertson et al 2013a;Reiners et al 2012) or the Mg ii infrared triplet (see e.g. Busà et al 2007;Pietarila & Livingston 2011).…”
Section: Introductionmentioning
confidence: 99%